Decoupling of CO2, CH4, and N2O agriculture emissions in the EU - Andrei, Jean Vasile; Avram, Sorin; Băncescu, Irina; Gâf Deac, Ioan I; Gheorghe, Carmen Adriana; Diaconu, Anișoara Ionela (Frontiers in Environmental Science, 2022)
This paper addresses the problem of CO2, CH4 and N2O emissions in EU for 2008-2018 period, and their contributing factors, through an extensive and complex analysis. The research incubated in the manuscript answers to the question whether new state members managed to catch up with old state members regarding technology innovation and mitigation of N2O emissions from agriculture activities. Methodology used includes Tapio decoupling index and metafrontier non-radial Malmquist N2O emission performance index. The paper considers short-term, medium-term and long term decoupling analysis. Results suggest a shift of decoupling status in worse for 2013-2018 period compared to 2008-2013 period which should concern low-carbon agriculture policy-makers. Also, it was noticed an increase in total-factor N2O emission performance for the 2008-2018 period. New state members managed to catch up with old state members regarding technology innovation and mitigation of N2O emissions from agriculture activities, however not all countries managed to do so. For example Romania has experienced an efficiency loss due to a technology change and from this perspective Romania should address first managing N2O and CO2 emissions. The findings extend the traditional framework of investigating the effects of the CO2, CH4 and N2O in agriculture and highlight the necessity of addressing environmental aspects from a broader perspective of the policymakers and to develop innovative decoupling indexes. The research investigation is reporting from a post-transition country by prioritizing the measures to be implemented.